Use of Sub-Surface Soil Water in Robusta Coffee Field Through Organic Matter Wicks - Pujiyanto Pujiyanto (Indonesian Coffee and Cocoa Research Institute, 2011)
One of the most important cocoa diseases is vascular streak dieback (VSD), caused by Oncobasidium theobromae. The serious attacks of this disease caused death of the plants more than 70%. Mechanical, culture technique, and chemical control still do not produce satisfactory result. Boron and silicon are essential elements potential to be used to improve natural resistance. This research was conducted to identify the effect of boron and silicon in controlling VSD attack and its effect on seedling growth. The research was conducted in Kaliwining Experimental Station of Indonesian Coffee and Cocoa Research Institute, Jember, East Java. The treatments was designed by randomized completely block design with two factors and five replications. The first factor was boron in form of H3BO3 and silicon in form of Si(OH)4. The second factor was concentrations of 75 ppm, 150 ppm, 300 ppm and 0 ppm as a control. The results showed that application of boron and silicon with foliar spray significantly improve those nutrients content in plant shoots. Application of boron improved polyphenol, cellulose and lignin content whereas application of silicon had no effect on the concentration of polyphenol and lignin, but concentration of 75 ppm increased cellulose content. Application of boron significantly decreased VSD disease on cocoa seedlings while application of silicon showed no significant effect on reducing the attack VSD disease. Boron application accelerated plant growth whereas silicon application did not retard seedling growth. Key words : Systemic, inducing, resistance, boron, silicon, VSD and cocoa.